Superfood and Functional Food The Development of Superfoods and Their Roles as Medicine - Shiomi, Naofumi; Waisundara, Viduranga (IntechOpen, 2017)
Superfoods and functional foods are receiving increasing attention because of their important roles in health. This book focuses on the production of superfoods and functional foods and their role as medicine. In the early chapters, prominent researchers introduce the roles and production of microalgae and functional fruits through metabolic engineering, the use of food waste, and effective cooking procedures. In the latter chapters, other prominent researchers introduce the medical effects of polyphenols, glutamine, and unsaturated fatty acids, which are contained in superfoods and functional foods. They suggest the importance of superfoods and functional foods in the treatment and prevention of many diseases. It is also recommended for readers to take a look at a related book, Superfood and Functional Food: An Overview of Their Processing and Utilization.